Mutation Analysis of MYORG in a Chinese Cohort With Primary Familial Brain Calcification - Zeng, Yi-Heng; Lin, Bi-Wei; Su, Hui-Zhen; Guo, Xin-Xin; Li, Yun-Lu; Lai, Lu-Lu; Chen, Wan-Jin; Zhao, Miao; Yao, Xiang-Ping (Frontiers in Genetics, 2021)
Primary familial brain calcification (PFBC) is a progressive neurological disorder manifesting bilateral brain calcifications in CT scanning with symptoms as parkinsonism, dystonia, ataxia, and psychiatric symptoms, etc. Recently, pathogenic variants in MYORG have been linked to autosomal recessive PFBC. This study aims to elucidate the mutational and clinical spectrum of MYORG mutations in a large cohort of Chinese PFBC patients with possibly autosomal recessive or absent family history. Mutational analyses of MYORG were performed by Sanger sequencing in a cohort of 245 PFBC patients including 21 subjects from 10 families compatible with a possibly autosomal-recessive trait and 224 apparently sporadic cases. In-depth phenotyping and neuroimaging features were investigated in all patients with novel MYORG variants. Two nonsense variants (c.442C>T, p.Q148*; c.972C>A, p.Y324*) and two missense variants (c.1969G>C, p.G657R; c.2033C>G, p.P678R) of MYORG were identified in four sporadic PFBC patients respectively. These four novel variants were absent in gnomAD and their amino acid were highly conserved, suggesting these variants have a pathogenic impact. Patients with MYORG variants tend to display a homogeneous clinical spectrum, showing extensive brain calcification and parkinsonism, dysarthria, ataxia, or vertigo. Our findings supported the pathogenic role of MYORG variants in PFBC and identified two pathogenic variants (c.442C>T, c.972C>A), one likely pathogenic variant (c.2033C>G), and one variant of uncertain significance (c.1969G>C), further expanding the genetic and phenotypic spectrum of PFBC-MYORG.